(untitled) (Vietnam Journal of Community Medicine, 2023)
Background: The “Global Student Health Behavior Survey” (GSHS) is designed to help countries measure and assess behavioral risk factors and protection for health among students aged 13 to 17 years old. Objectives: Analysis of some related factors with the health behavior of middle and high school students in Hanoi in 2022. Methods: Cross-sectional survey. Results and conclusion: Gender, age group, alcohol use, smoking, and exposure to smokers are statistically significant factors related to the health behavior of students aged 13-17 years old. Although some students’ health behaviors have improved compared to GSHS 2019 in Vietnam, they are still high and need further intervention to improve, such as Drinking beer (38.1%), smoking (7.8%), using carbonated soft drinks (34.1%), consuming fast food at least 3 days/week (12.6%) and not exercising (26.5%)